An integrated solution to harvest the waste heat from a large marine solid oxide fuel cell. (1st November 2020) - Ouyang, Tiancheng; Zhao, Zhongkai; Su, Zixiang; Lu, Jie; Wang, Zhiping; Huang, Haozhong
Graphical abstract: Highlights: A novel system combined SOFC and waste heat recovery system is proposed. Supercritical-CO2 and Kalina cycles are integrated to realize cascade utilization. The zeotropic working fluids are used in supercritical-CO2 recompression cycle. The combined system improves fuel efficiency by 38.86%. The economic performance of the system is analyzed. Abstract: The substantial use of fossil fuels in marine transportation aggravates the problems of energy shortage and environmental pollution. The application of fuel cell and waste heat recovery technology in ships can effectively address this severe global issue. In this study, a novel combined system comprising a solid oxide fuel cell–gas turbine subsystem, supercritical-carbon dioxide recompression cycle, and Kalina cycle is introduced and analyzed. First, the feasibility of each model is verified by comparing the subsystems with results in the literature. Subsequently, zeotropic working fluids are used in the supercritical-carbon dioxide recompression cycle. Then, the optimum composition and ratio of working fluids in the bottoming cycles are determined by simulation. Finally, the thermodynamic and economic properties are simulated and analyzed. The results illustrate that the actual power output and thermal efficiency of this combined system can reach 286.41 kW and 71.37%, respectively. The latter is 38.65% higher than the efficiency of a solid oxide fuel cell. In addition, the maximum cost recovery time of the waste heat recovery system is 7.492 year, which completely satisfies the economic requirements. To summarize, the proposed novel system design exhibits characteristics of high efficiency and cleanliness and is a better option for marine power generation equipment.